Bibliometric and visual analysis of Kawasaki disease in children from 2012 to 2022 - Cui, Zhengjiu; Luo, Fei; Wang, Jinjuan; Diao, Juanjuan; Pan, Yueli (Frontiers in Pediatrics, 2023)
Background: In recent years, the incidence of Kawasaki disease among the pediatric population has experienced a significant increase. With complications mainly affecting the cardiovascular system, Kawasaki disease has received widespread attention from scholars worldwide. Numerous articles on Kawasaki disease in children have been published far. However, there is a lack of studies that use visualization methods to perform a bibliometric analysis of the relevant literature.This study aims to obtain overall information on the output characteristics of publications on childhood Kawasaki disease between 2012 and 2022 through bibliometric analysis, identify research hotspots and frontiers, and provide new ideas and references for future clinical and scientific research.Methods: Literature meeting the inclusion criteria was screened from the Web of Science Core Collection, PubMed, and Scopus databases. Visual analysis of the literature by country, institution, journal, author, keywords, and references was performed using Citespace (6.1.R6), VOSviewer (1.6.18), and the online bibliometric website (https://bibliometric.com/).: A total of 4867 eligible publications were included. The number of annual publications is generally rising, rapidly increasing since 2019. Among countries and institutions, China and KAOHSIUNG CHANG GUNG MEMORIAL HOSPITAL have the highest output of articles. With 104 publications, Ho-Chang Kuo has a high impact in the field of KD. The most cited author is Jane W. Newburger. The most prolific journal is FRONTIERS IN PEDIATRICS. CIRCULATION is the most frequently co-cited journal. The most popular keyword in frequency and centrality is "immunoglobulin." The reference with the highest burst intensity was Verdoni L, LANCET, 2020.2 Conclusion: Kawasaki disease in children remains a hot topic among pediatricians worldwide and is receiving increasing attention. We innovated the "national-institutional-journal" model, which promotes further international cooperation in this field. The hot topics in the field of pediatric KD are "KD pathogenesis," "immunoglobulin resistance and complementary therapy," and "cardiovascular complications." Frontiers include disease-related ("multisystem inflammatory syndrome," "coronavirus disease 2019," "hypotension"), treatment-related ("procalcitonin," " anakinra"), and pathogenesis ("polymerase chain reaction").